(untitled) (The Pakistan Development Review, 2015)
Income inequality is rising in Germany. This is true for both functional as well as personal income distribution. After reunification in 1990, a general increase in inequality can be observed. This trend becomes particularly pronounced in the 2000s. In the literature on financialisation a link between the developments in the financial sector, the financing behaviour of firms, and income distribution is established. Also, in the varieties of capitalism literature a connection between the prevailing institutions, among them the financial institutions, and the tendency of an economy towards higher or lower inequality is made. This study attempts to investigate if changes in the financial sphere may have caused the higher inequality in Germany. There are different ways in which the financial sector could have contributed to the increased inequality. Growth of the financial sector or large increases in incomes paid in this sector could lead to higher inequality directly. Alternatively, different behaviour of financial institutions and new financial actors could affect distribution in the non-financial sector so that the financial sector indirectly affects inequality.